Ecological and Faunistic Features of Helminths in Cattle in Uzbekistan (Journal of Pharmaceutical Negative Results, 2022)
This article involves the fauna and ecological features of helminths of cattle in various biocenoses of Uzbekistan. Based on many years of our own research and analysis of literature data, 71 species of helminths were identified in cattle of Uzbekistan, of which 12 species belong to the class of cestodes, 12 species to trematodes and 47 species to nematodes. Of the 71 species of helminths identified in cattle of the Republic, 1 species (Stephanofilaria assamensis) was noted by us for the first time in the CIS and 11 species (Moniezia alba, Trichocephalus globulosa, Bunostomum trigonocephalum, Camelostrongylus mentulatus, Cooperia punctate, C. pectinata, Grosspiculagia occidentalis, Nematodirus abnormalis, N. spathiger, Stephanofilaria assamensis, Thelazia skrjabini) in Uzbekistan. Among the identified parasitic worms of cattle in Uzbekistan, 37 species develop in a direct way, i.e. they develop without the participation of intermediate hosts. The remaining 34 species of helminths develop with the participation of intermediate and additional hosts. Their intermediate and additional hosts are freshwater and land mollusks, oribatid mites, grasshoppers, ants, dipterous insects, predatory mammals, and humans. Also, it was determined that of the 71 species of helminths Paramphistomum ichikawai, Taeniarhynchus saginatus, Trichocephalus globulosa, Aonchotheca bovis, Thelazia rhodesi, Th. gulosa, Th. skrjabini, Th. Petrovi, Onchocerca lienalis, Stephanofilaria stilesi and S. assamensis parasitize only cattle. Under the conditions of Uzbekistan, the total infection of cattle with helminths is 94.3%. At the same time, in some regions of Uzbekistan, infection of cattle with trematodes ranges from -34.0 to 66.6%, cestodes from 17.6 to 45.1% and nematodes from 70.0 % to 93.5 %. Among the widespread helminthiases of cattle that adversely affect their productivity are monieziosis, fascioliasis, paramphistomidiasis, trichuriasis, hemonchosis, parabronemiasis, thelaziosis, stephanofilariasis and other helminthiases.